PERKEMBANGAN OLAHRAGA TRADISIONAL PACU JALUR DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI PERIODE 2007-2013 - Yudi Putra Yudi Putra; Drs. Slamet, M.Kes '; Saripin, M.Kes, AIFO ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problems raised in this research is,the first how the development of traditional pacu jalur sport in the kecamatan kuantan mudik 2007-20013.The secont how prosedures for runway pacu jalur sport s in the kecamatan kuantan mudik 2007-2013.The third how public participation in the runway pac jalr sport kuantan mudik the period 2007-2013. This kind research using methods deskriptif.That is research in stack be based on the characteristics be oriented of the exiting data process of acquiring efforts.Techniques used in this research is,obsevation is with direct supervision of the development of racing sport in the district lines kuantan mudik.The Interviews to collect more accrate data. The authors conduted interview with respondents.Population taken in this research consisted of eighteen the head of the village, a tourism department head,and three commnity leaders. The sample in this research is a village head,tourism department head,and community leaders. Based on the results of the interview can be concluded that the former track racing a means of transportation and also show the social status,because only the ruler area,nobility and progenitor grandfather who was driving the boat. Then that part is not only for transportation ,but also in the speed race through a contest called racing track. Keywords: Traditional Sport Racing Track